Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Show that. (9p – 5q)^2+ 180pq = (9p + 5q)^2 Show that. (9p – 5q)^2+ 180pq = (9p + 5q)^2

Show that.  
 (9p – 5q)^2+ 180pq = (9p + 5q)^2
Show that.  
 (9p – 5q)^2+ 180pq = (9p + 5q)^2

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5859 Points
2 months ago
Dear Student

LHS = (9p–5q)^2+ 180pq
= 81p^2- 90pq + 25q^2+ 180pq
= 81p^2+ 90pq + 25q^2
RHS = (9p + 5q)^2
= 81p^2+ 90pq + 25q^2
LHS = RHS

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free